A Giant Epidermal Cyst of the Gluteal Region - Perek, Asiye; Yurdacan, Müge; Bölükoğlu, Yunus Emre; Durgun, Vedat (Cerrahpaşa Medical Journal, 2021)
Epidermal cysts are located subcutaneously and intradermally as well as in deeper anatomical areas, and they are the most common type of cysts in the subcutaneous tissue. They are typically small and are considered to be slow-growing palpable masses. The size of epidermal cysts is usually less than 5 cm. They may occur in any part of the body, especially on the head, neck, and trunk. We present a case of a 30-year-old woman with a giant mass in her right gluteal region. Magnetic resonance imaging and ultrasonography were performed. They revealed a large cystic lesion measuring 16×13×8 cm. The sac and all of its contents were excised under general anesthesia. To our knowledge, it is the largest epidermal inclusion cyst reported in the Turkish literature. Cite this article as: Perek A, Yurdacan M, Bölükoğlu YE, Durgun V. A Giant Epidermal Cyst of the Gluteal Region. Cerrahpaşa Med J 2021; 45(1): 60-63.